A novel information exchange method for industrial heterogeneous fieldbuses. (19th December 2013) - Li, Z.H.; He, C.; Song, T.; Shao, C.; An, Y.
The information integration of industrial control systems is the basis for optimising productive process and improving management efficiency, and it requires the reliable and real–time information exchange among heterogeneous industrial fieldbuses. In this paper, a novel information exchange method is proposed, and a multi–protocol gateway with the hardware interfaces of different buses is designed. This method is composed of two parts: the process–level device and the multi–protocol gateway communication managements. It adopts the data mapping mechanism and the command priority queue to realise reading and writing communication. The experiment with an industrial electrostatic precipitator demonstrates that the proposed method can achieve non–conflict and efficient information exchange in the heterogeneous fieldbus system.